2016
DOI: 10.3390/md14110202
|View full text |Cite
|
Sign up to set email alerts
|

New Typical Vector of Neurotoxin β-N-Methylamino-l-Alanine (BMAA) in the Marine Benthic Ecosystem

Abstract: The neurotoxin β-N-methylamino-l-alanine (BMAA) has been identified as an environmental factor triggering neurodegenerative diseases such as Amyotrophic Lateral Sclerosis (ALS) and Alzheimer’s disease (AD). We investigated the possible vectors of BMAA and its isomers 2,4-diaminobutyric acid (DAB) and N-2(aminoethyl)glycine (AEG) in marine mollusks collected from the Chinese coast. Sixty-eight samples of marine mollusks were collected along the Chinese coast in 2016, and were analyzed by an HILIC-MS/MS (hydroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In China, 68 samples from 29 species originating from aquaculture and bought at local markets of several towns were analyzed in a study graded B [ 58 ]. The presence of free BMAA in 5 of the 68 edible mollusks from three marine species was reported: one mussel ( Mytilus coruscus 0.45 mg kg −1 FW) sample out of nine, one razor clam ( Solen strictus 0.66 mg kg −1 FW) out of one, and three gastropods ( Neverita didyma up to 3.97 mg kg −1 FW) out of five analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In China, 68 samples from 29 species originating from aquaculture and bought at local markets of several towns were analyzed in a study graded B [ 58 ]. The presence of free BMAA in 5 of the 68 edible mollusks from three marine species was reported: one mussel ( Mytilus coruscus 0.45 mg kg −1 FW) sample out of nine, one razor clam ( Solen strictus 0.66 mg kg −1 FW) out of one, and three gastropods ( Neverita didyma up to 3.97 mg kg −1 FW) out of five analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…To assess health risk associated with BMAA-containing food, it is of great importance that data includes all the BMAA fractions (free, soluble or precipitated-bound, or total). Most of the studies we graded A and B report the total BMAA content in edible organisms, few of them [ 23 , 24 , 43 , 44 , 54 , 58 ] report both the total and free BMAA contents, or both the total soluble and free BMAA contents [ 23 , 24 , 43 , 44 , 54 , 58 ]. In these last studies, the total soluble BMAA content far exceeds that of free BMAA (e.g., maximum of 2.45 mg total BMAA kg −1 FW against 0.2 mg free BMAA kg −1 FW in mussels) [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BMAA has been hypothesized to trigger the pathogenesis of neurodegenerative diseases like Amyotrophic Lateral Sclerosis (ALS) and Alzheimer's disease (AD). Extensive in vitro experiments have demonstrated that the neurotoxicity of BMAA for neurons is a result of multiple mechanisms including action on glutamate receptors to induce oxidative stress in the neuron by depleting glutathione and generating a cytotoxic DNA damaging alkylating agent [60,61] . Study with vervets showed that BMAA may trigger neurodegenerative disease such as Alzheimer's Disease as a result of gene/environment interaction, thus it could became a useful tool for studying of neurodegenerative disease [62,63] .…”
Section: Marine Neurotoxins Interacting With Other Receptorsmentioning
confidence: 99%